Lifecycle Management of Hydrogen Pipelines: Design, Maintenance, and Rehabilitation Strategies for Canada’s Clean Energy Transition - Myo Myo Khaing; Shunde Yin (Energies)
This paper examines the crucial elements of pipeline-based hydrogen transportation, highlighting the particular difficulties and technical developments required to guarantee the sustainable, effective, and safe supply of hydrogen. This study lists the essential phases of hydrogen pipeline management, from design to repair, as the relevance of hydrogen infrastructure in the worldwide energy transition continues to rise. It discusses the upkeep, monitoring, operation, and rehabilitation procedures for aged pipelines with an emphasis on the cutting-edge techniques and technology used to mitigate the dangers related to hydrogen’s unique features, such as leakage and embrittlement. Together with highlighting the legislative and regulatory frameworks that enable the infrastructure, this paper also discusses the material, economic, and environmental difficulties related to hydrogen pipelines. Lastly, it emphasizes how crucial it is to fund research, create cutting-edge materials, and implement sophisticated monitoring systems to guarantee the long-term dependability and safety of hydrogen pipelines. These initiatives will be crucial in allowing hydrogen’s contribution to the future of renewable energy, together with international collaboration on regulatory standards.